2018
DOI: 10.9755/ejfa.2017.v29.i12.1565
|View full text |Cite
|
Sign up to set email alerts
|

Juçara (Euterpe edulis) pulp as a substrate for probiotic bacteria fermentation: Optimisation process and antioxidant activity

Abstract: Juçara fruit (Euterpe edulis) has received considerable attention because of its high content of phenolic compounds. However, its suitability as a matrix for probiotic bacteria is not known yet. The objective of this study was to evaluate the pH and temperature conditions for the fermentation in juçara pulp by Lactobacillus reuteri and Lactobacillus plantarum. The optimised conditions were determined by central composite rotational design, and used for the analysis of cellular viability, sugar content, pH, lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Guergoletto et al (21) indicated that different vegetables, including bananas, can be sufficient substrates for the growth of lactic acid bacteria, especially species of Lactobacillus bacteria. They also reported a difference in the consumption of sugar content in the fermented juçara pulp according to the species of Lactobacillus bacteria, which makes the fermentation periods different and results in differences in the production of lactic acid.…”
Section: Figure 1 the Viability Of Probiotics After Fermentation For ...mentioning
confidence: 99%
“…Guergoletto et al (21) indicated that different vegetables, including bananas, can be sufficient substrates for the growth of lactic acid bacteria, especially species of Lactobacillus bacteria. They also reported a difference in the consumption of sugar content in the fermented juçara pulp according to the species of Lactobacillus bacteria, which makes the fermentation periods different and results in differences in the production of lactic acid.…”
Section: Figure 1 the Viability Of Probiotics After Fermentation For ...mentioning
confidence: 99%
“…in fermented jabuticaba. Since the fermentation of jabuticaba can potentialize its antioxidant activity, that confers benefits to human health and in the industrial field, this study is necessary to evaluate the fermentation parameters in order to optimize maceration time to produce fermented jabuticaba with better acceptability and nutritional quality (Guergoletto et al, 2017).…”
Section: Maceration Time Over Antioxidant Activity Volatile Compounds...mentioning
confidence: 99%
“…In general, the aroma of fermented beverages is the result of the balance of various volatile compounds and its composition is determined mainly by the fruit's genotype and fermentation process (Ouyang et al, 2017). The harmony of these components is critical to maintain the beverage nutritional value and quality (Guergoletto et al, 2017).…”
Section: Maceration Time Over Antioxidant Activity Volatile Compounds...mentioning
confidence: 99%